Five Senses Windmill: An Innovative Edutainment Learning Media Integrating Local Wisdom to Enhance Conceptual Understanding in Students with Intellectual Disabilities - Vina Fitria Azmi; Siska Desy Fatmaryanti; Nur Ngazizah (Integrated Science Education Journal, 2026)
Purpose of the study: This study develops and validates the Five Senses Windmill, an innovative edutainment-based learning media integrating local wisdom, designed to enhance conceptual understanding and active engagement among students with intellectual disabilities in Special Needs Schools. Methodology: Employing Research and Development (R&D) with the ADDIE model, this study systematically developed the media through five phases: Analysis, Design, Development, Implementation, and Evaluation. Media and content validity were assessed using Aiken's V (≥0.80), with instrument reliability reaching 0.87 (Cronbach's Alpha). Three fourth-grade students with mild intellectual disabilities participated in purposive sampling trials. Data collection involved expert validation, pre-post testing, structured observations, and teacher interviews. Quantitative analysis measured validity and effectiveness through N-gain calculations, while qualitative analysis explored learning dynamics and engagement patterns. Main Findings: The Five Senses Windmill demonstrated high validity (Aiken's V = 0.91) and proved effective in improving students' conceptual understanding with moderate-to-high effectiveness (N-Gain = 64.5%). Students showed significant improvement in identifying sensory functions, increased from passive dependency to active participation, and demonstrated enhanced confidence in applying concepts to daily life. The bamboo-based media successfully integrated visual, kinesthetic, and cultural elements, creating meaningful learning experiences. Positive teacher responses confirmed the media's practicality and ease of implementation. Novelty/Originality of this study: This study uniquely combines edutainment pedagogy with Indonesian local wisdom through sustainable bamboo materials, addressing the gap in holistic, multisensory, culturally-responsive learning media for students with intellectual disabilities. The windmill's interactive design simultaneously develops cognitive, affective, and psychomotor domains while fostering cultural identity and environmental awareness.